Preparation of PBT/clay nanocomposites using supercritical process - Hong, Youngki; Yoon, Ho Gyu; Lim, Soonho (International journal of precision engineering and manufacturing, 2009)
Butylene terephthalate cyclic (BTC) oligomers have been successfully polymerized to a poly(buthylene terephthalate) (PBT) employing the advantages of the low viscosity of cyclic oligomers and high solubility, high transport property of supercritical fluids. The ring-opening polymerization of BTC oligomers initiated by various mol concentration of catalyst (cyclic stannoxane 1) is carried out in supercritical chlorodifluoromethane (HCFC-22) at temperature ranging from 160 to 220 °C, at pressure ranging from 150 to 410 bar and at time ranging from 2 to 10 hrs. The highest molecular weight was obtained at 190 °C, 410 bar and 4 mol% mol concentration of catalyst. The results of XRD and TEM show that some of clays are intercalated or disordered, consisting of about 2–10 parallel silicate layers to form morphology like thin thread and some of clays are collapsed. The modulus and tensile strength of the nanocomposites prepared by supercritical process were higher than those of nanocomposites prepared by melt process.